The forgotten waltz eaudiobook - Enright, Anne (Recorded Books Inc., 2011)
Irish novelist Anne Enright won the coveted Man Booker Prize for her eloquent novel The Gathering. In The Forgotten Waltz, Enright crafts a stunning tale about a Dublin woman's affair and its heartrending consequences. Gina Moynihan is already married when she meets SeAn Vallely. But longing and desire soon overtake them-and their lives begin to crumble shortly after. "A breathtaking work that will surprise you; highly recommended."-Library Journal